Nucleosynthesis in Outflows from Black Hole–Neutron Star Merger Disks with Full GR(ν)RMHD - Sanjana Curtis; Jonah M. Miller; Carla Fröhlich; Trevor Sprouse; Nicole Lloyd-Ronning; Matthew Mumpower (The Astrophysical Journal Letters, 2023)
Along with binary neutron star mergers, the inspiral and merger of a black hole and a neutron star is a predicted site of r -process nucleosynthesis and associated kilonovae. For the right mass ratio, very large amounts of neutron-rich material (relative to the dynamical ejecta) may become unbound from the post-merger accretion disk. We simulate a suite of four post-merger disks with three-dimensional general-relativistic magnetohydrodynamics with time-dependent Monte Carlo neutrino transport. We find that within 10 ^4 GM _BH / c ^3 (∼200–500 ms), the outflows from these disks are very close to the threshold conditions for robust r -process nucleosynthesis. For these conditions, the detailed properties of the outflow determine whether a full r -process can or cannot occur, implying that a wide range of observable phenomena is possible. We show that on average the disk outflow lanthanide fraction is suppressed relative to the solar isotopic pattern. In combination with the dynamical ejecta, these outflows imply a kilonova with both blue and red components.